Bio-optical characterization of offshore NW Mediterranean waters: CDOM contribution to the absorption budget and diffuse attenuation of downwelling irradiance. (August 2016) - Pérez, Gonzalo L.; Galí, Martí; Royer, Sarah-Jeanne; Sarmento, Hugo; Gasol, Josep M.; Marrasé, Cèlia; Simó, Rafel
Abstract: We investigated the peculiar bio-optical characteristics of the Mediterranean Sea focusing on the spectral diffuse attenuation coefficient [Kd (λ)] and its relationship with chlorophyll a concentration (Chl a ), complemented with measurements of light absorption by chromophoric dissolved organic matter (CDOM) and the optical properties of particulate material. The non-water absorption budget showed that CDOM was the largest contributor in the 300–600 nm range (>60% of the absorption at 443 nm in the euphotic layer), increasing to 80% within the first optical depth (FOD). This translated into CDOM accounting for >50% of KdBio (λ) (the irradiance attenuation coefficient caused by all non-water absorptions) between 320 and 555 nm and throughout both layers (FOD and euphotic). Indeed, we tested three Chl a -based bio-optical models and all three underestimated Kd (λ), evidencing the importance of CDOM beside Chl a to fully account for light attenuation. The Morel & Maritorena (2001) model (M&M 01) underestimated Kd (λ) in the UV and blue spectral regions within the FOD layer, showing lower differences with increasing wavelengths. The Morel et al. (2007a) model (BGS 07) also underestimated Kd (λ) in the FOD layer, yet it performed much better in the 380–555 nm range. In the euphotic layer, the Morel (1988) model (JGR 88) underestimated Kd ( λ) showing higher differences at 412 and 443 nm and also performed better at higher wavelengths. Observed euphotic layer depths (Z1% ) were 28 m shallower than those predicted with the M&M 01 empirical relationship, further highlighting the role of CDOM in the bio-optical peculiarity of Mediterranean Sea. In situ measurements of the CDOM index (Φ), an indicator of the deviation of the CDOM-Chl a average relationship for Case 1 waters, gave a mean of 5.9 in the FOD, consistent with simultaneous estimates from MODIS (4.8±0.4). The implications of the bio-optical anomaly for ecological and biogeochemical inferences in the Mediterranean Sea are discussed. Highlights: In NW offshore Mediterranean waters the non-water absorption was dominated by CDOM. CDOM ruled the contribution to KdBio (λ) in the FOD and euphotic layer, >80% at UV. The M&M 01 model underestimated Kd (λ) in the UV-blue regions for the FOD layer. CDOM´s role in the bio-optical anomaly was proven by in situ and MODIS appraisals. Using Chl a -based models for Kd (λ) in these waters could lead to important flaws.